2010
DOI: 10.1007/s00441-010-0964-x
|View full text |Cite
|
Sign up to set email alerts
|

Smell with new neurons

Abstract: In this minireview, we briefly describe some recent discoveries of new neurons that are generated inside adult mammalian olfactory circuits and that might affect olfactory function and related behaviors. These studies indicate potential new directions for the investigation of olfactory perception, the examination of olfactory disorders, and the development of related treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
(45 reference statements)
0
4
0
1
Order By: Relevance
“…The new neurons generated in hippocampus is important for learning and memory [1], as well as emotion state regulation [5,31], while the ventricular zone-generated new neurons migrate into a range of brain regions including olfactory bulb, hypothalamus, amygdala and piriform cortex, contributing to olfaction [14,40,43], defending the virus infection [16], and metabolism regulation [41]. Adult neurogenesis is also proposed as an important mechanism to repair the brain after injury or to maintain the brain plasticity in different circumstances [2,16,42].…”
Section: Introductionmentioning
confidence: 99%
“…The new neurons generated in hippocampus is important for learning and memory [1], as well as emotion state regulation [5,31], while the ventricular zone-generated new neurons migrate into a range of brain regions including olfactory bulb, hypothalamus, amygdala and piriform cortex, contributing to olfaction [14,40,43], defending the virus infection [16], and metabolism regulation [41]. Adult neurogenesis is also proposed as an important mechanism to repair the brain after injury or to maintain the brain plasticity in different circumstances [2,16,42].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of olfactory receptors, this means that specific odorant molecules differing in binding energy thresholds may combine synchronically and, together, represent the "odor-image" of a given umwelt, On higher hierarchical levels, cell-to-cell relationships are also explored through developmentally adaptable mechanisms and semiotic perceptual learning. It has been recently observed that olfaction is influenced by newly born neurons and that adult neurogenesis is conditioned by both training and/or environmental exposure (Yuan, 2010). This is a clear example illustrating how adult neurogenesis and olfactory perceptual learning are reciprocally dependent on each other.…”
Section: Biosemiotic Analysismentioning
confidence: 95%
“…Jedną z niezwykłych cech systemu węchowego jest jego zdolność do regeneracji neuronów czuciowych nabłonka węchowego (olfactory epithelium -OE). Neurogeneza zachodzi zarówno w OE, jak i w opuszce węchowej (olfactory bulb -OB), a nowo powstałe neurony mogą migrować do obszarów peryferyjnych, stając się interneuronami, ziarnami (granule) i komórkami glomerularnymi (Yuan 2010). Szacuje się, że receptory węchu i smaku regenerują się co sześćdziesiąt dni (Doetsch i wsp.…”
Section: Introductionunclassified